Linking Leaf Water Potential, Photosynthesis and Chlorophyll Loss With Mechanisms of Photo- and Antioxidant Protection in Juvenile Olive Trees Subjected to Severe Drought - Baccari, Sahar; Elloumi, Olfa; Chaari-Rkhis, Anissa; Fenollosa, Erola; Morales, Melanie; Drira, Noureddine; Ben Abdallah, Ferjani; Fki, Lotfi; Munné-Bosch, Sergi (Frontiers in Plant Science, 2020)
The identification of drought-tolerant olive tree genotypes has become an urgent requirement to develop sustainable agriculture in dry lands. However, physiological markers linking drought tolerance with mechanistic effects operating at the cellular level are still lacking, in particular under severe stress, despite the urgent need to develop these tools in the current frame of global change. In this context, one-year-old olive plants growing in the greenhouse and with a high intra-specific variability (using various genotypes obtained either from cuttings or seeds) were evaluated for drought tolerance under severe stress. Growth, plant water status, net photosynthesis rates, chlorophyll contents and the extent of photo- and antioxidant defenses (including the de-epoxidation state of the xan-thophyll cycle, and the contents of carotenoids and vitamin E) were evaluated under well-watered conditions and severe stress (by withholding water for 60 days). Plants were able to continue photosynthesizing under severe stress, even at very low leaf water potential of −4 to −6 MPa. This ability was achieved, at least in part, by the activation of photo- and antioxidant mechanisms, including not only increased xanthophyll cycle de-epoxidation, but also enhanced α-tocopherol contents. ‘Zarrazi’ (obtained from seeds) and ‘Chemlali’ (obtained from cuttings) showed better performance under severe water stress compared to the other genotypes, which was associated to their ability to trigger a higher antioxidant protection. It is concluded that (i) drought tolerance among the various genotypes tested is associated with antioxidant protection in olive trees, (ii) the extent of xanthophyll cycle de-epoxidation is strongly inversely related to photosynthetic rates, and (iii) vitamin E accumulation is sharply induced upon severe chloro-phyll degradation.